Morphological and molecular characterization of coprinoid fungi newly recorded for the mycobiota of Iran - Seidmohammadi, Elham; Abbasi, Saeed; Asef, Mohammad Reza (Cellular and Molecular Biology, 2018)
Twenty-five specimens of coprinoid fungi were collected during an ongoing survey of agaric fungi in Kermanshah Province, western Iran. The specimens were identified based on morphological characteristics and molecular analysis of internal transcribed spacer sequences. Five species of Coprinellus viz C. disseminates, C. flocculosus, C. micaceus, C. radians and C. xanthothrix, three species of Coprinopsis viz C. atramentaria, C. insignis and C. semitalis and two species of Coprinus viz C. pinetorum and C. sterquilinus were identified. Among the species identified in this research, three unreported species from Iran namely C. insignis, C. semitalis and C. pinetorum are reported. Detailed morphological descriptions and illustrations of this three newly-recorded species were provided here and their evolutionary relationships were presented by the constructing of a phylogenetic tree.